Land of milk and honey - Zhang, C Pam (Riverhead Books, 2023)
"About a Chinese American chef who, lured to a decadent, enigmatic colony of the superrich in a near future in which food is disappearing, discovers the meaning of pleasure and the ethics of who gets to enjoy it, altering her life and, indirectly, the world"--